'A Twisted, Looping Form': Staging dark ecologies in Ella Hickson's Oil. (17th February 2020) - Lonergan, Patrick
Abstract : In Dark Ecology (2016), Timothy Morton argues that one of the challenges presented by the impact of human activity upon the environment is that '[w]e are faced with the task of thinking at temporal and spatial scales that are unfamiliar, even monstrously gigantic' (25). The advent of the Anthropocene era thus requires us to understand the agency of the individual in the context of a geological epoch that will persist for thousands of generations, and which seems likely to outlast the human species itself. This paper considers how theatrical form is being used to register the sense of 'weirdness' (to use Morton's word) that arises from this awareness, exploring representations of stage time in plays that dramatize ecological themes. These include work by Mike Bartlett and Caryl Churchill, but the primary focus is on Ella Hickson's Oil (2016), a play that explores humanity's shifting approaches to carbon-based energy from the late 1890s to the early 2050s, but which has a protagonist whose age increases only by approximately sixty years during that period. By using stage time metonymically to consider the relationship between the length of a human life and the progression of the natural world over centuries, Hickson shows that one function of art in the Anthropocene might be to demonstrate the impact of human activity across 'monstrously gigantic' spans of time and space. She also explores how the concept of theatrical realism may be an impediment to the formation of a necessary ecological awareness, demonstrating how experimental approaches to theatrical form may offer us new ways of understanding contemporary environmental and political concerns. By placing those achievements in the context of Morton's ideas about looping and weirdness, the paper concludes that that Hickson's Oil is using theatrical form to think deeply about dark ecology and its temporal consequences.